2015
DOI: 10.1179/1074935714z.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

Improving arm function in chronic stroke: a pilot study of sensory amplitude electrical stimulation via glove electrode during task-specific training

Abstract: Combining task-specific training with glove-based SES in chronic stroke resulted in changes in arm sensation and function that were maintained at 3-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The results can be attributed to specificity of the intervention, which involved repeated practice of elbow extension while promoting speed and movement accuracy. The results were consistent with studies which reported that task specific training produced statically significant and clinically relevant improvements in the upper extremity motor recovery of the patients with stroke [ 35 ] and Sullivan et al who stated that task specific training in chronic stroke resulted in changes in arm sensation and function that were maintained at 3-month follow-up [ 36 ].…”
Section: Impact Of Task Specific Trainingsupporting
confidence: 90%
“…The results can be attributed to specificity of the intervention, which involved repeated practice of elbow extension while promoting speed and movement accuracy. The results were consistent with studies which reported that task specific training produced statically significant and clinically relevant improvements in the upper extremity motor recovery of the patients with stroke [ 35 ] and Sullivan et al who stated that task specific training in chronic stroke resulted in changes in arm sensation and function that were maintained at 3-month follow-up [ 36 ].…”
Section: Impact Of Task Specific Trainingsupporting
confidence: 90%
“…For a rehabilitation modality to be successful, it needs to fulfill certain practical criteria: considering the importance of starting the rehabilitation after stroke as early as possible, [55][56][57] the easyaccessible and low-cost elastic resistance used in this study provides an attractive solution. Furthermore, recent reviews highlight the positive relationship between the amount of therapy and therapy outcomes, 58,59 emphasizing the importance of both the dose-response and dose-timing relationships between stroke therapy and clinically meaningful improvements.…”
Section: Practical Application and Perspectivesmentioning
confidence: 99%
“…Several studies have investigated self-directed [17], supervised [18] or self-administered [19][20][21][22] upper limb therapy on people with stroke [23][24][25]. The studies investigated several techniques including the use of novel robotic systems [26][27][28] to deliver rehabilitation therapies at home [29][30][31][32][33][34]. The results from most of these studies showed that stroke participants improved in several outcomes including ADL performance, which were maintained for several weeks.…”
Section: Introductionmentioning
confidence: 99%